1973
DOI: 10.1002/aja.1001380407
|View full text |Cite
|
Sign up to set email alerts
|

The corticotroph of the rat adenohypophysis: A comparative study

Abstract: The immunological and cytological specificity of antiserum to adrenocorticotrophic hormone was established and the corticotroph defined at the light microscopic level by immunocytochemistry. Our observations substantiated recent reports by several investigators. By comparing thin methacrylate sections with adjacent 1 p-methacrylate sections immunochemically stained with anti-ACTH, the ACTH cell was identified at the ultrastructural level and its morphology studied. Using the criteria established at light and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Baker (2) reported that some ACTH cells could be stained with AF and PAS reaction at the light microscopic level. Bowie et al (6) also reported that the secretory granules of the ACTH cell are responsible for the positive PAS reaction of the methacrylate sections for electron microscopy. Such an inconstant reaction to the PAS technique may be responsible for the physiological condition of ACTH cell.…”
Section: Tsh Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baker (2) reported that some ACTH cells could be stained with AF and PAS reaction at the light microscopic level. Bowie et al (6) also reported that the secretory granules of the ACTH cell are responsible for the positive PAS reaction of the methacrylate sections for electron microscopy. Such an inconstant reaction to the PAS technique may be responsible for the physiological condition of ACTH cell.…”
Section: Tsh Cellsmentioning
confidence: 99%
“…To date, however, methodologic difficulties have prevented application of this technique to distinguish between the ACTH and TSH cell types at electron microscopic resolution (6,17,18,24,26 Two groups of adult male rats of the Wistar strain were used. The control group consisted of untreated rats, and the other group consisted of rats sacrificed at 1, 3, 5 and 7 days after adrenalectomy.…”
mentioning
confidence: 99%
“…There have been several studies concerning the ultra structure of the corticotrophs of rat anterior pituitary both in normal and adrenalectomized animals [1][2][3][4][5]. Among them, Nakayama et al |1] and Kurosumi et al [5] pre sented quantitative data that the secretory granules of the corticotrophs decreased in number and that the ratio of immature/mature granules increased after adrenalec tomy.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical evidence sustains the genuine ACTH secretion from the Siperstein's cells (Moriarty and Halmi, 1972;Bowie et al, 1973;Moriarty et al, 1975). We intend to present an innovation on the differentiation of F-S cells in the gland, and the present electron microscopy (teals with the substantial existence of various types of F-S cells involving a corticotroph.…”
mentioning
confidence: 99%